Правові напрями й особливості оновлення українського регулювання скидання забруднювальних речовин - Уберман, В. І.; Васьковець, Людмила Антонівна (Національний університет "Одеська юридична академія", 2023)
Досліджено головний правовий засіб забезпечення якості поверхневих вод екологічного законодавства України: лімітаційне регулювання скидання забруднювальних речовин (ЗР) з точкових джерел (РСЗР). Удосконалення РСЗР вимагається доктринальними природоохоронними документами. Зазначено, що РСЗР існує в українському водному законодавстві у майже незмінному вигляді біля 60 років, ґрунтується на застарілих екологічних уявленнях, еколого-політичних та еколого-економічних принципах, містить помилки і вимагає реформування та оновлення. Цілями змін є забезпечення дотримання вимог актів українського водного і екологічного законодавства, створення умов для наближення до європейського водного законодавства та дій у післявоєнний відновлюваний період. Виявлено, що при використанні поняття ЗР не враховується його релятивність. Констатується, що поняття «водна екосистема» та її властивості «асиміляційна спроможність» (АС) і «самоочисна здатність» (СЗ), через які здійснюється РСЗР, не відображено у водному законодавстві. Зазначено, що першочергові зміни мають стосуватися понятійного апарату Водного кодексу України. У його регулятивних нормах необхідно встановити вимоги до складових законодавчого механізму РСЗР, а у підзаконних нормативно-правових актах – до операційних методичних засобів та екологічних властивостей водних об’єктів, до інструментів регулювання складу та якості поверхневих вод. До таких належать: об’єкти регулювання – ЗР з урахуванням їх релятивності; екологічні фактори впливу на склад води – АС і СЗ; інструменти регулювання – нормативи ГДС, зона змішування; вимоги до результатів – ЕНЯВ та нормативи ГДК. Доведено, що басейновий принцип визначення нормативів ГДС не відповідає вимогам законодавства. Напрями змін визначаються: 1) невиявленими раніше прогалинами, розбіжностями та помилками в актах водного законодавства; 2) політикою адаптації до acquis ЄС; 3) кризовим погіршенням екологічної безпеки водокористування в умовах воєнного стану та необхідністю післявоєнного відновлення економіки.

The article investigates the main legal means of ensuring the quality of surface waters included in the environmental protection legislation of Ukraine, namely limiting the regulation of pollutant discharges (PD) from point sources (RPD). It states that according to the requirements of Ukrainian doctrinal documents, the current legislative sub-institute of the RPD requires significant improvement and changes. It noted that the RPD has existed in Ukrainian water legislation for 60 years in almost unchanged form. RPD is based on outdated environmental saving ideas, realized olden environmentalpolitical and environmental-economic principles, includes heavy errors, and requires reform and updating. The goals of the proposed changes are to ensure compliance with the requirements of Ukrainian water and environmental legislation, to create conditions for approximation to European water legislation, and to take renovate actions in the postwar reconstruction period. Founded that under using Ukrainian term of “polluting substances” (PS) its relativity property do not taken into account. It is noted that the concept of “aquatic ecosystem” and its main properties, “assimilation capacity” (AC) and “self-purification possibility” (SPP), through which the RPD is carried out, are not reflected in the water legislation. The article notes that the priority changes should concern the conceptual apparatus of the Water Code of Ukraine (WCU). Proposed to establish in the WCU the requirements for regulatory norms and for the components of the RPD legislative mechanism to include in bylaw acts the main environmental properties of water bodies, as well as the methodological tools and the legal instruments for regulating the composition and quality of surface waters. RPD’s legislative mechanism includes: objects of regulation, i.e., PS, taking into account their relativity property; environmental factors affecting the composition of water, namely AC and SPP; regulatory tools, i.e. MAD standards and mixing zones for discharges; requirements for the results of regulating, i.e., water quality standards and MAC standards. Also proved that the “Basin Principle of MAD Standards Determining”, which is the main calculation method for PS limit discharges, does not meet the requirements of Ukrainian legislation. Proposed such kinds of changes in WCU and in bylaw acts that take into account the following circumstances: 1) previously undetected gaps, discrepancies, and errors in acts of water legislation; 2) updating the policy of adaptation to the EU acquis; 3) the crisis deterioration of the environmental safety of water use in the conditions of Ukrainian martial law and the need for post-war recovery of the economy.
Legal directions and peculiarities of renewal of the Ukrainian regulation for discharging of pollutants
Keywords: екологічне та водне законодавство України; водне законодавство ЄС; спеціальне водокористування; забруднення поверхневих вод; регулювання якості води; порівняльне право; environmental and water legislation of Ukraine; EU water legislation; surface water pollution; water quality regulation; comparative law